Revealing Argumentation Skills of High School Students in Biology Learning through Toulmin Argumentation Pattern - Nining Sahara H A Rawe; Siti Zubaidah; Hendra Susanto (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Argumentation skills are one of the skills that students must have in the 21st century.Â Â Argumentation skills are important to develop because they can train students to communicate effectively in education, especially in science learning. This study aims to determine the description of students' argumentation skills, especially in biology subjects on environmental change material. The type of research used is descriptive quantitative using essay tests. 51 high school X-grade students were selected as samples in this study. The validity value of each item instrument is 0.403-0.596, meaning that all instrument items are said to be valid. The reliability result of the instrument is q = 0.736 (Cronbac's Alpha>0.60), so the instrument used is reliable. The results showed that the argumentation ability of students of the claim component was included in the highest component, with 66.2%, followed by the data component 23%, warrant 5.9%, backing 2%, and rebuttal 0% and the level of argumentation ability of students was still at level 1-2, the argumentation ability of students using claims, level 1 as much as (67.5%), supported by evidence, level 2 as much as (11.75%), warrants, level 3 as much as (2%), backing, level 4 as much as (0.5%), while the appearance of qualifiers and rebuttal, level 5 as much as (0%). The results show that there is a need for more attention to students through future research efforts should focus on implementing interventions to improve argumentation skills in students such as structured debates or problem-based learning and other learning models. It is important for students and teachers to collaborate with each other in honing argumentation skills to improve the quality of learning.